Pengaruh Permainan Boy-Boyan Terhadap Kemampuan Lari Sprint Siswa Kelas V Di UPT SD Negeri 060885 Medan Baru - Natalia Br Sinukaban; Khairul Usman; Winara; Try Wahyu Purnomo; Sri Mustika Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Boy-Boyan game on the sprinting ability of fifth-grade students at UPT SD Negeri 060885 Medan Baru. The study employs a quantitative approach using a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The sample consisted of 24 fifth-grade students selected using the total sampling technique. Data collection involved a 60-meter sprint test to measure completion time and a rubric to assess sprinting technique covering the starting technique, body position, leg movement, arm swing, movement coordination, and the finish-line technique. Data analysis was conducted using the Shapiro-Wilk normality test, Levene’s homogeneity test, and the Wilcoxon Signed-Ranks Test, assisted by IBM SPSS Statistics 32 software. The results indicate that the average sprint completion time decreased from 12.27 seconds in the pretest to 11.40 seconds in the posttest, representing a 7.16% improvement. Additionally, the average score for sprinting technique increased from 13.29 to 19.00, an improvement of 42.97%. The Wilcoxon test results showed an Asymp. Sig. (2-tailed) value of <0.001 (p<0.05), indicating a significant difference between the pretest and posttest. Thus, the Boy-Boyan game has a significant effect on improving the sprinting ability of fifth-grade students, in terms of both speed and technical quality. The Boy-Boyan game can serve as an effective and enjoyable alternative for Physical Education (PJOK) instruction that enhances the motor skills of elementary school students.